2009
DOI: 10.1016/j.mod.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of beta-1,4-galactosyltransferase 2 during medaka (Oryzias latipes) gastrulation

Abstract: Glycans are known to play important roles in vertebrate development; however, it is difficult to analyze in mammals because it takes place in utero. Therefore, we used medaka (Oryzias latipes) to clarify the roles of glycans during vertebrate development. beta-1,4-Galactosyltransferase is one of the key enzymes in the biosynthesis of the lactosamine structures that are commonly found on glycoproteins and glycolipids. Here, we show the essential role of beta4GalT2 during medaka development. Depletion of beta4Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Interestingly, in the mopholino treated embryos, laminin was hypo-galactosylated and hence could explain the decreased in ectodermal cell migration of [94]. β4Gal-T2: Tonoyama, et al showed that β4Gal-T2 was indispensable for mediolateral cell intercalation and thus extension movement during gastrulation [95]. The specific substrates for β4Gal-T2 activity in glycoproteins responsible for these ef-fects are currently not known but has been speculated to be related with N-glycosylated FGF receptor signaling.…”
Section: β4galts Deficiency In Fishmentioning
confidence: 99%
“…Interestingly, in the mopholino treated embryos, laminin was hypo-galactosylated and hence could explain the decreased in ectodermal cell migration of [94]. β4Gal-T2: Tonoyama, et al showed that β4Gal-T2 was indispensable for mediolateral cell intercalation and thus extension movement during gastrulation [95]. The specific substrates for β4Gal-T2 activity in glycoproteins responsible for these ef-fects are currently not known but has been speculated to be related with N-glycosylated FGF receptor signaling.…”
Section: β4galts Deficiency In Fishmentioning
confidence: 99%
“…Mislocalization of glycosyltransferases within the Golgi can have profound effects on glycan synthesis and in turn on the normal physiology of cells. The cell biological, developmental, and physiological significance of the action of glycosyltransferases is highlighted by the consequences of deletion or knock-down of members of this protein family, which results in developmental anomalies as well as in congenital defects in glycosylation (CDG) in humans [1,[16][17][18][19][20][21][22][23].…”
Section: Overview Of Er-golgi Transport Of Glycosyltransferasesmentioning
confidence: 99%
“…5; data not shown) analyses revealed that a group of at least 24 glycosyltransferases (see Table S6 in the supplementary material) exhibits either a DrV (15) or VrD (9) profile. Sugar epitope modification of receptor and extracellular molecules has been reported to modulate signaling activities in many other systems (Haecker et al, 2008;Machingo et al, 2006;Tonoyama et al, 2009). Given that several major signaling pathways are key components in the regulation of positional identities in the streak, it is not surprising that we found these 24 enzymes exhibiting differential levels of expression in the streak, representing both early and late steps of O-linked and N-linked glycosyl modification.…”
Section: Research Articlementioning
confidence: 99%